The Rheology And Handling Of Laterite Slurries - Peter V. Avotins; Steven S. Ahlschlager; Gordon R. Wicker (Society for Mining, Metallurgy & Exploration, 1979)
Laterite ore slurries exhibit Bingham plastic behavior and can be characterized by the magnitude of their yield point and Bingham viscosity. These two parameters are affected by ore composition, solids concentration, and temperature and are used to predict the pressure drop in pipelines and heat transfer coefficients in shell-and-tube heat exchangers. In cycloning of laterite slurries, the calculated cut size is corrected by factors obtained from the rheological parameters.